Step-by-step explanation:
We know that f(x) = - x² + x - 6
Then, we can find f(x + h) as follows:
f(x + h) = -(x + h)² + (x + h) - 6
f(x + h) = -(x² + 2xh + h²) + x + h - 6
f(x + h) = -x² - 2xh - h² + x + h - 6
Then, we can find the difference quotient as
![(f(x+h)-f(x))/(h)=\frac{(-x^2-2xh-h^2+x+h-6)-(-x^2+x-6)_{}}{h}](https://img.qammunity.org/2023/formulas/mathematics/college/tb0cv7tx6u39bl7wv3776pa7bfqdze150s.png)
Simplifying, we get:
![\begin{gathered} =(-x^2-2xh-h^2+x+h-6+x^2-x+6)/(h) \\ =(-2xh-h^2+h)/(h) \\ =-2x-h+1 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/d861s1vevues521ava9wqfwd55g1lny9qj.png)
Therefore, the answer is
![undefined]()